Techniques for live capture of deepwater fishes with special emphasis on the design and application of a low‐cost hyperbaric chamber - J. E. Smiley; M. A. Drawbridge (Journal of Fish Biology, 2007)
A cost effective, simple, portable hyperbaric chamber was constructed from polyvinyl chloride to aid in the collection of adult rockfishes Sebastes sp. to hold as broodstock. This system was designed to recompress fishes quickly once brought to the surface on hook and line, and to allow for decompression over a period of days. The hyperbaric chamber is capable of continuous stable operation at −2 and can accommodate fishes up to 91·4 cm in length and 26·8 cm in diameter. Pressure in the chamber is maintained by a Goulds Booster pump that delivers continuous pressure and supplies sea water at a rate of 3·8 to 7·6 l min −1 to as many as four chambers. The hyperbaric chamber operated very effectively and allowed successful decompression of 12 cowcod Sebastes levis captured at depths of 90·2 to 146·3 m.